REFORMULASI KEDUDUKAN JANDA CERAI MATI DALAM HUKUM WARIS ADAT BATAK PERSPEKTIF GENDER - Sihotang, Amri Panahatan; Izziyana, Wafda Vivid (EGALITA, 2023)
The Toba Batak Community's customary law is one of the customary laws that is still alive with a kinship system that follows the father's lineage (patrilineal) which differentiates the position of sons and daughters. This research uses empirical methods. The results of the research explain that the position of widows and daughters in the Toba Batak tribe according to customary law is not as heirs, but based on the Supreme Court decision no. 179K/Sip/1961 Dated 23-10-1961 based on a sense of humanity and general justice, as well as on the nature of equal rights between women and men, the equal position between men and women can be seen in Presidential Instruction No. 9 of 2000 concerning Gender Mainstreaming in National Development. The Position of Divorced Widows in Batak Customary Inheritance Law. Gender Perspective. In the patrilineal kinship system adopted by Batak society, men are placed in a higher position. Societies that adhere to a partial kinship system of women have a very low position, so it is necessary to reformulate the position of women in the field of customary law, by establishing a national customary law of inheritance that is bilateral in nature